Contemplation and "Non-doing" in the Christian Tradition: The Case of John of Ruusbroec - Faesen, Rob (Entangled Religions, 2023)
A recurrent theme in many forms of contemplative practice is the need to come to a state of outward solitude (i.e., being without distractions); this provides a framework for contemplation, which ultimately can give way to a suspension of all efforts, opening up a state of inner letting-be. This contribution explores these elements in the Christian tradition following the Biblical typology of Martha and Mary (Lk 10:38-42) with some leading authors (Clement of Alexandria, Ambrose of Milan, Augustine of Hippo, John Cassian and Gregory the Great). A specific aspect of the Christian interpretation is that the state of ‘non-doing’ is essentially relational. This relational dimension, in which contemplation and the state of ‘letting-be’ are understood as a response to the initiative of the divine Other who is ‘the origin’ (Lat. principium), provides John of Ruusbroec with the basis to explain how action and non-doing (i.e., contemplation) can coalesce perfectly.